PERBEDAAN BILANGAN PEROKSIDA PADA MINYAK JELANTAH SETELAH PENAMBAHAN BUBUK KULIT MANGGIS (Garcinia Mangostana Linn) - dhyana putri (Jurnal Skala Husada : The Journal of Health, 2018)
AbstractBackground Damage to oil during the frying process caused by the oxidation process, it will affect the quality and nutritional value of the food that fried, and it can cause a variety of diseases such as the deposition of fat in the blood vessels and the possibility of carcinogenic compounds that can cause cancer. The rate of oxidation of the oil can be inhibited by the addition of antioxidants. Antioxidants retard oxidation or free radicals from oxidized fats. As a natural antioxidant, mangosteen pericarp contains xanthones that are very effective in preventing the occurrence of free radicals. The problem in this study is whether there is a difference numbers peroxide in used cooking oils after addition of the mangosteen pericarp powdered? Objective The purpose of research is to know the difference peroxide used cooking oil after the addition of the mangosteen pericarp powdered.Methods This type of research is True Exsperiment Design by Design Post Test Only with Control Design. The treatments were the addition of the mangosteen pericarp powdered in some concentration : 0.10%, 0.20%, 0.30%, 0.40% and 0.50%, and the soaking time mangosteen pericarp powder on used cooking oil during one day, two days and three days. The analysis was conducted using peroxide iodometri. Data analysis was conducted by using One Way Anova. followed by Least Significant Different (LSD).Result Data analysis showed a significant difference peroxide in used cooking oils after addition of mangosteen pericarp powder at various concentrations. Conclusions The most effective concentration is 0.30%, and the soaking time is one  day. Keywords: Numbers peroxide, mangosteen pericarp